Eksploitasi Perempuan di Media Massa - Athirah binti Muhamad Suhaili, Hafizah; Zehan binti Jehan Sher, Nur; Norhidayat, Norhidayat; Fadillah, Rahmat (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Exploitation in the mass media can carry the meaning of the utilization of the female-quarantined group carried out on official channels that are used as a means of communication for everyone for the benefit of the market. The exploitation of women's bodies in the mass media is a common phenomenon in this contemporary era. Then, this research will involve a process in which there is a process of simplifying words in order to explain the data obtained while practicing a conceptual approach. This research was conducted with a literature study. The result of the research is also that the Women's group is created with extraordinary attractiveness from various aspects as previously presented. As for the attractiveness if it falls into the wrong hands, it will apply the name of exploitation of women in the mass media. This is not something that should be accepted but everyone needs to be aware that this is wrong in terms of religion because women seem to be made tools whereas in Islam, women are created beautiful to be glorified and not to be exploited. Keywords: Attractiveness, Exploitation, Mass Media, Women Abstrak Eksploitasi di media massa bisa membawa arti pemanfaatan ke atas golongan yang berjantina Perempuan yang dilakukan pada saluran resmi yang dijadikan alat komunikasi bagi setiap orang demi bagi kepentingan pasar. Eksploitasi tubuh perempuan dalam media massa merupakan fenomena yang umum terjadi di era kontemporer ini. Lalu, penelitian ini bakal melibatkan sebuah proses di mana ada berlakunya proses penyederhanaan kata dalam rangka menjelaskan data yang didapat sekaligus mempraktik pendekatan konseptual. Penelitian ini dilakukan dengan studi kepustakaan. Hasil penelitiannya pula adalah, golongan Perempuan tercipta dengan daya tarik yang luar biasa dari berbagai aspek seperti yang telah tersajikan sebelumnya. Adapun daya Tarik tersebut jika jatuh pada tangan yang salah maka akan berlakulah yang namanya eksploitasi Perempuan di media massa. Hal ini bukanlah hal yang seharusnya diterima baik melainkan setiap orang perlu ada kesadaran bahwa hal tersebut adalah salah di sisi agama karena golongan Perempuan seakan-akan dibuat alat padahal dalam Islam, Perempuan diciptakan indah untuk dimuliakan dan bukan untuk dieksploitasi. Kata Kunci : Daya Tarik, Eksploitasi, Media Massa, Perempuan